Impact of Improved Diagnosis and Treatment on Holistic CKD Burden - Navdeep Tangri; Stacey Priest; Anthony Zara; Bo Ren Long; Jieling Chen; Naveen Rao; Clélia-Elsa Froguel; Breonny Robson; Nick Guldemond; Matthew Eckelman; Ana Flavia Moura; Ralph Audehm; et al. (Kidney International Reports)
Introduction: Chronic kidney disease (CKD) is an underdiagnosed and undertreated disease despite the availability of effective interventions. The potential clinical, economic, and environmental impacts of increased diagnosis and improved adherence to guideline-directed medical therapies (GDMTs) recommended for patients with CKD are not well-understood. Methods: Eight country populations (Australia, Brazil, China, Germany, The Netherlands, Spain, UK, and USA) were simulated for 25 years using the IMPACT CKD model to compare burdens under various diagnosis and GDMT adherence scenarios versus current practice. GDMT consisted of kidney protecting, glucose lowering, lipid lowering, as well as antihypertensive and lifestyle interventions. Patients could be treated with 1 or multiple therapies, if eligible, and no guideline changes occurred over the time horizon. Treatment effects were assumed multiplicative. Results: Scenarios with improved GDMT adherence projected cumulative decreases in dialysis, cardiovascular (CV) events, and death by −3.2% to −23.2%, −12.2% to −41.4%, and −2.3% to −9.3%, respectively, compared with current practice over 10 years. Because of delayed CKD progression, kidney replacement therapy (KRT) costs and environmental burden were also projected to decrease by −2.5% to −19.4% and −2.7% to −21.2%, respectively, compared with current practice. All treatment scenarios predicted greater improvements over 25 years, underscoring the long-term impact of CKD, and highlighting the importance of early intervention. Conclusion: Differences in projected impacts between countries are multifactorial, though they are sensitive to demographics and health care systems. Implementation of policies that lead to improved detection and treatment of CKD are urgently required across the globe to mitigate the growing burdens of CKD on patients and caregivers, health care systems, society, and our environment.